(untitled) (UNED Research Journal, 2019)
Introduction: The production of butterflies is an important socioeconomic activity and has become an option to generate income for rural microenterprises. Objective: To see how farming affects the body size of Heliconius butteflies in Costa Rican farms. Methods: We measured adults and pupae of Heliconius cydno, H. erato, H. hecale and H. melpomene in 10 butterfly farms, in the Huetar Atlantic Region of Costa Rica. Results: In some farms, adult Heliconius erato and H. hecale are heavier (p≤ 0.05), and have a longer abdomen and larger forewings. The weight did not differ among farms, and the sex ratio is close to 0,5. Conclusion: All farms sampled produce butterflies of fit for commercialization.